2021
DOI: 10.1007/s11356-021-15433-w
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term statistical assessment of meteorological indicators and COVID-19 outbreak in hot and arid climate, Bahrain

Abstract: The COVID-19 pandemic has significantly impacted the global lifestyle, and the spreading of the virus is unprecedented. This study is aimed at assessing the association between the meteorological indicators such as air temperature (°C), relative humidity (%), wind speed (w/s), solar radiation, and PM 2.5 with the COVID-19 infected cases in the hot, arid climate of Bahrain. Kendall and Spearman rank correlation coefficients and quantile on quantile regression were used as main econometric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Coccia, 2021 [ 27 ] conducted a study in Italy, found that about 75% of individuals infected and 81% of deaths during the first wave of COVID-19 pandemic were in industrial areas with high air pollution. Furthermore, Qaid et al, 2021 [ 28 ] reported that PM2.5 has a relationship with the COVID-19 infected cases. Similarly, Bashir et al, 2020 [ 29 ] established a relationship and found that “PM10, PM2.5, SO 2 , NO 2 , and CO were linked with the COVID-19 epidemic in California”.…”
Section: Discussionmentioning
confidence: 99%
“…Coccia, 2021 [ 27 ] conducted a study in Italy, found that about 75% of individuals infected and 81% of deaths during the first wave of COVID-19 pandemic were in industrial areas with high air pollution. Furthermore, Qaid et al, 2021 [ 28 ] reported that PM2.5 has a relationship with the COVID-19 infected cases. Similarly, Bashir et al, 2020 [ 29 ] established a relationship and found that “PM10, PM2.5, SO 2 , NO 2 , and CO were linked with the COVID-19 epidemic in California”.…”
Section: Discussionmentioning
confidence: 99%
“…As of March 21, 2022, there were 469,713,452 confirmed cases, including 6,074,560 fatalities (WHO 2021 ). In addition to massive loss of life, the global economy is estimated to shrink by 6%, and at least 300 million people became unemployed (Qaid et al 2022 ; Bashir et al 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“…While human‐to‐human transmission has received enormous attention, 13 studies have identified other conditions which contribute to the spread of COVID‐19 in some countries 13–15 . For example, in Bahrain, 16 Brazil, 17 China, 18 Germany, 19 and the United States, 20–23 climate conditions and environmental pollution have emerged as conditions which may facilitate the spread of the disease. For example, temperature, air quality, humidity, and wind speed correlate with an increase in COVID‐19 infections; specifically, an exponential increase in the number of cases as temperatures decrease or humidity increases.…”
Section: Introductionmentioning
confidence: 99%